Out-of-pocket costs and productivity losses in haemodialysis and peritoneal dialysis from a patient interview survey in Taiwan. Issue 3 (23rd March 2019) - Tang, Chao-Hsiun; Chen, Hsi-Hsien; Wu, Ming-Ju; Hsu, Bang-Gee; Tsai, Jer-Chia; Kuo, Chi-Cheng; Lin, Shih-Pi; Chen, Tso-Hsiao; Sue, Yuh-Mou
Abstract : Objectives: The total medical (economic) costs of haemodialysis (HD) and peritoneal dialysis (PD), including direct medical costs, out-of-pocket (OOP) costs and productivity losses, have become an important issue. This study aims to compare the direct non-medical costs and indirect medical costs of both modalities in Taiwan. Design and setting: This multicentre study included cross-sectional interviews of patients over 20 years old and articulate, who had been continuously receiving long-term HD or PD for more than 3 months between April 2015 and March 2016. Mann-Whitney U test, Wilcoxon rank-sum test and 1000 bootstrap procedures with replacement were used for analysis. Outcome measures: Differences in OOP costs and productivity losses. Results: There were 308 HD and 246 PD patients available for analysis. HD patients had significantly higher monthly OOP costs than PD patients after bootstrap procedures (NTD 5912 vs NTD 5225, p<0.001; NTD, new Taiwan dollars; 1 US dollar=30 NTD). Compared with PD patients, HD patients had higher monthly productivity losses after bootstrap procedures (NTD 14 150 vs NTD 11 611, p<0.001), resulting from more time spent seeking outpatient care (HD, 70.4 hours vs PD, 4.4 hours, p<0.001) and time spent by family caregivers for outpatient care (HD, 66.1 hours vs PD, 6.1 hours, p<0.001). The total costs per patient–month of HD and PD modalities, including OOP costs and productivity losses, were NTD 20 062 and NTD 16 836, respectively. Conclusions: The HD modality has higher OOP costs and productivity losses than the PD modality in Taiwan.